Validation of a prodrug formulation for bromoform to reduce enteric methane in ruminants - M. Myers; N. Tomkins; S. Payne; Mozumder; M.J. Callaghan (Animal Feed Science and Technology, 2026)

Global patterns and regional insights into kelp forest protection, restoration, and stewardship - Aaron M. Eger; Adriana Verges; Akshata MehtaFalkland Islands; Albert Pessarrodona; Alejandra Mora-Soto; Alejandro Bernal-Ibáñez; Aleksandra Smorygo; Alexandria M. Niese; Alexis Savard-Drouin; Andrew Kalani Carlson; Ang Put; Annalisa Falace; et al. (Journal of Applied Phycology, 2026)
Kelp forests are among the most extensive and productive coastal ecosystems, yet they remain underrepresented in global conservation policy despite widespread declines driven by interacting global- (i.e., ocean warming, marine heatwaves) to local-scale stressors. At the same time, kelp conservation and restoration efforts are expanding rapidly across regions, but measures of success and syntheses tend to primarily focus on ecological conditions and trends, not on conservation and restoration actions. To fill this gap, we developed a comparative global dataset of kelp conservation initiatives based on expert-derived regional narratives from 209 participants spanning 35 regions with kelp forests. We applied a structured presence–absence scoring framework across six domains: conservation actions, restoration approaches, governance actors, conservation objectives, social dimensions, and funding structures, supplemented by regional expert knowledge to enable cross-regional comparison. Across regions, conservation was characterised by strong emphasis on monitoring (86% of regions), multi-actor governance (scientific institutions 94%, government agencies 86%), and protecting existing forests (66%), while active restoration was undertaken in half of the regions. Social engagement (66%) and links to fisheries and livelihoods (69%) were widespread, whereas explicit climate adaptation objectives were less common (17%). We identify a set of conservation profiles that describe how kelp forest conservation is advancing in different ecological and governance contexts worldwide. These findings highlight that scaling kelp conservation is as dependent on the social, financial, institutional, and policy systems that govern implementation, as it is on ecological knowledge and technical capacity. By bridging regional knowledge with global analysis, this study provides a framework for aligning locally grounded conservation action with global biodiversity targets.

Between-day fluctuations in seated low back pain are linked to seated spine movements - Jessa M. Davidson; Erinn McCreath Frangakis; Jack P. Callaghan (Next Research, 2026)

The sensory and ripening characteristics of Cheddar cheese manufactured within a multispecies sward dairy food system - Richard M. Page; Maurice G. O'Sullivan; Brendan Horan; David T. Mannion; Kieran N. Kilcawley; Iwona Skibinska; Alann Jezequel; John T. Tobin; James A. O'Mahony; Tom F. O'Callaghan; Prabin Lamichhane (International Dairy Journal, 2026)

Activated carbon stabilises bromoform and is an effective carrier for methane mitigation in vitro - M. Myers; N. Tomkins; S. Payne; Mozumder; A. Singh; M.J. Callaghan (Animal Feed Science and Technology, 2026)

Proportion of native plants is a key predictor of pollinator richness in urban greenspaces - Thomas Lilkendey; Brittany M. Mason; Nadja Pernat; Marina Marquis; Jacob S. Francis; Corey T. Callaghan (Urban Ecosystems, 2025)

The impact of high rainfall events on the submesoscale salinity field in a coastal sea: Greater Cook Strait, New Zealand - Khushboo Jhugroo; Joanne M. O'Callaghan; Craig L. Stevens (New Zealand Journal of Marine and Freshwater Research, 2025)
River inflow into the coastal oceanic environment can result in low salinity submesoscale features (LSMFs). The enhanced water column stability sustained within these coherent structures affects local biological productivity. With‐event and seasonal variability of LSMFs were investigated in a coastal sea — Greater Cook Strait — that is characterised by strong tidal and wind forcing as well as being forced at the land‐sea boundary by several major rivers. A combination of ocean glider and satellite observations revealed the existence of seasonal variability in temperature, chlorophyll and stratification in LSMFs. High rainfall from ex‐cyclone enhanced production of LSMFs in seasons when they would otherwise be less frequent. Stronger stratification was observed at the end of spring, in summer and at the beginning of autumn both in ambient shelf conditions and within LSMFs. Subsurface chlorophyll‐a maxima were found associated with summer and spring LSMFs, when temperature had a stronger contribution to vertical stratification. In the available samples, LSMFs were advected seawards when river discharges exceeded 600 m s . When river flows were lower than this threshold, other drivers such as wind or currents were required to advect the observed LSMFs offshore.

Humpback whale (Megaptera novaeangliae) maturity and body condition in Ireland, Norway and Cabo Verde based on UAS photogrammetry data - Miguel Blázquez; Nick Massett; Seán O’Callaghan; Marcus Hogan; Pedro López-Suárez; Katia Lopes; Pádraig Whooley; Joanne M. O’Brien; Frederick W. Wenzel; Ian O’Connor; Simon D. Berrow (Frontiers in Marine Science, 2025)
Animal morphometrics are essential for understanding a species’ life history and its ecological interactions with the environment. This study investigates the maturity status and body condition of humpback whales ( Megaptera novaeangliae ) across understudied areas of the Northeastern Atlantic Ocean. Uncrewed Aerial Systems (UAS or drones) were used to collect photogrammetry data from humpback whales in Ireland, Norway, and Cabo Verde between 2022 and 2024. Body length and condition metrics were derived from aerial imagery and analyzed using Bayesian modeling to estimate and propagate measurement uncertainty. The resulting measurements were evaluated to infer maturity status, migratory patterns, and habitat use. Photogrammetric measurements indicated potential variability in whale body length and condition across study areas, with individuals in Cabo Verde appearing larger and in better condition. In Irish waters, body length was positively correlated with offshore habitat preference, while shorter (younger) individuals tended to inhabit nearshore waters, potentially increasing their exposure to anthropogenic pressures. Additionally, body condition improved intra-seasonally at both the population and individual levels in Irish waters. These findings demonstrate the utility of UAS photogrammetry for assessing the maturity and body condition of humpback whales across diverse habitats. The observed geographical and temporal trends in condition provide valuable insights into habitat use and underscore the importance of Ireland as a feeding ground in the Northeastern Atlantic. This study also highlights the value of UAS photogrammetry in advancing our understanding of baleen whale population ecology in understudied regions, providing relevant information for species conservation and management.

Metabolic profiling of bovine colostrum: unravelling the influences of diet and seasonality on functional dairy components - Raghunath Pariyani; Gabriele Rocchetti; Aidan Lawless; Michael Dineen; Neil Maher; Lorraine M. Bateman; Luigi Lucini; Tom F. O'Callaghan (Food Chemistry, 2025)

The impacts of a multispecies sward grazing system and stage of lactation on the processing-efficiency and compositional characteristics of milk and Cheddar cheese - Richard M. Page; Brendan Horan; John T. Tobin; David T. Mannion; Kieran N. Kilcawley; Iwona Skibinska; Alann Jezequel; James A. O'Mahony; Tom F. O'Callaghan; Prabin Lamichhane (International Dairy Journal, 2025)

High‐Integrity Forests Are Critical for Forest Specialist Birds - Corey T. Callaghan; Ruben Venegas‐Li; Brittany M. Mason; Richard A. Fuller; Rebecca Spake; James E. M. Watson (Global Ecology and Biogeography, 2025)
Aim Efforts to retain and restore forest integrity—the degree to which a forest's structure and function are not modified by humans—are increasingly underpinning global biodiversity conservation efforts. However, there is still much uncertainty around how species respond to changes in forest integrity. Geographically variable responses would have consequences for conservation planning assessments and targeted conservation action. Our goal was to quantify the relationship between forest integrity and bird diversity. Location Global; 98 bioregions. Time Period 2017–2020. Major Taxa Studied Birds. Methods By integrating global‐scale spatially explicit forest landscape integrity data with a citizen science bird dataset, we provide the first empirical assessment of the relationship between forest integrity and bird diversity. Results We found that both species richness and abundance of forest specialists had a positive association with integrity. However, the relationship between forest integrity and bird diversity varied across bioregions, with bioregions at low latitudes tending to have more positive relationships between forest integrity and species richness. Of the 74 bioregions assessed, 64% had more than half of their species favouring high integrity forests. Main Conclusions These results support calls for the targeted protection of the world's remaining high‐integrity forests but also showcase that consideration must be given to restoring forest integrity where possible.

Overlapping turbulent boundary layers in an energetic coastal sea - Arnaud F. Valcarcel; Craig L. Stevens; Joanne M. O'Callaghan; Sutara H. Suanda (Ocean Science, 2025)
Turbulent mixing properties were directly observed to understand the interactions and overlapping events of wind-forced and tidally forced boundary layers in a deep, weakly stratified coastal sea. Te-Moana-o-Raukawa / Cook Strait of Aotearoa / New Zealand is an 𝒪(200 m) deep, energetic strait, known to experience both strong tidal currents and high wind speeds. More than 𝒪(40 000) quality-controlled turbulence observations were obtained from an ocean glider equipped with a microstructure profiler and a current speed through water sensor. Tidal flows of 𝒪(1 m s−1) and wind speeds of 𝒪(10 m s−1) independently enhanced turbulent dissipation to ϵ=O(10-5Wkg-1) in bottom and surface mixed layers. Over a 4 d period, boundary-generated turbulence was evident in the interior water column on 10 occasions, enhancing interior diapycnal diffusivity levels by 5–35-fold, reaching Kz=𝒪(0.1–1 m2 s−1). In three instances, the surface and bottom mixed layers overlapped. These overlapping boundary layers were present in water depths 5-fold deeper than previously observed, which has implications for the vertical extent of material fluxes from the surface or seafloor. Interior stratification was transient, emerging from far-field advection of low-density surface water, and supported by vertical buoyancy fluxes that were episodically eroded by boundary-generated turbulence. Combining observations with one-dimensional General Ocean Turbulence Model (GOTM) outputs, turbulence interactions in the interior were found to be modulated by wind, tides, and transient stratification fields, in turn influencing the vertical structure of sinks and sources of turbulent kinetic energy. Enhanced vertical transport toward the interior of the near-boundary shear-produced turbulence was found to erode interior stratification. The interplay between antecedent stratification, turbulence generation, and vertical transport allows boundary layers to interact and modulate the vertical structure of seawater properties in deep coastal passages.

Spatial patterns and interactions among multiple cultural ecosystem services across urban greenspaces - Haojie Cao; Nataly G. Miguez; Brittany M. Mason; Corey T. Callaghan; Jiangxiao Qiu (Ecosystem Services, 2025)

Urban greenspaces benefit both human utility and biodiversity - Nataly G. Miguez; Brittany M. Mason; Jiangxiao Qiu; Haojie Cao; Corey T. Callaghan (Urban Forestry & Urban Greening, 2025)

Impacts of N-(n-Butyl)thiophosphoric triamide (NBPT) on the physicochemical properties of milk protein isolate (MPI) dispersions: A study on micelle integrity - Maria P. Byrne; Patrick J. Forrestal; Tom F. O’ Callaghan; Niharika Rahman; Aishwarya Ray; Martin Danaher; Bernard M. Corrigan; Noel A. McCarthy; Chikere G. Nkwonta; Karl Richards; Farhad Garavand; Enda Cummins; et al. (Food Structure, 2025)

Integrated testing and modelling of substructures using full-field imaging and data fusion - Tobias Laux; Riccardo Cappello; Jack S. Callaghan; Geir Ólafsson; Stephen W. Boyd; Duncan A. Crump; Andrew F. Robinson; Ole T. Thomsen; Janice M. Dulieu-Barton (Engineering Structures, 2025)

Evidence for low bioavailability of dietary nanoparticulate cerium in a freshwater food chain - Lisa A. Golding; Paul Callaghan; Brad M. Angel; Graeme E. Batley; Grant Griffiths; An Nguyen; Tom Cresswell (Aquatic Toxicology, 2025)

Evidence-base for urban green-blue infrastructure to support insect diversity - Diana E. Bowler; Corey T. Callaghan; Jéssica F. Felappi; Brittany M. Mason; Robin Hutchinson; Prashant Kumar; Laurence Jones (Urban Ecosystems, 2025)
Green-blue urban infrastructures potentially offer win-win benefits for people and nature in urban areas. Given increasing evidence of widespread declines of insects, as well as their ecological importance, there is a need to better understand the potential role of green-blue urban infrastructure for insect conservation. In this review, we evaluated 201 studies about the ability of green-blue infrastructure to support insect diversity. Most studies were focused on the role of local and landscape-level characteristics of green-blue infrastructure. Fewer studies explicitly compared one type of infrastructure to another, and even fewer compared insect communities between green-blue infrastructure and traditional infrastructure. Overall, the body of research highlights the importance of plant diversity and reduced intensity of management (e.g., mowing) for most insect taxon groups. While local characteristics seem to be generally more important than landscape factors, insect communities within green-blue infrastructures can also depend on their connectivity and landscape context. Some infrastructure types are generally more beneficial than others; for instance, ground-level habitats tend to support more insects than green roofs. Few studies simultaneously studied synergies or trade-offs with other services provided by green-blue infrastructure, but environmental variables, such as tree cover and plant diversity, that affect insects are likely to also affect the provision of other services such as improving thermal comfort and the well-being of people. Our review offers some initial evidence for how green-blue infrastructure could be designed for multifunctionality with insects in mind.

Bio-degradable ‘reef bags’ used for rubble stabilisation and their impact on rubble stability, binding, coral recruitment and fish occupancy - Tania M. Kenyon; Conor Jones; David Rissik; Wills Brassil; David Callaghan; Neil Mattocks; Tom E. Baldock (Ecological Engineering, 2025)

Cheddar cheese production, structure and in-vitro semi-dynamic gastric digestion: The role of β-casein phenotype - Davor Daniloski; Richard M. Page; Prabin Lamichhane; Conor J. Fitzpatrick; Todor Vasiljevic; André Brodkorb; Mark Timlin; John Paul Murphy; Tom F. O'Callaghan; Noel A. McCarthy (Food Research International, 2024)

Riverine concentrations and export of dissolved silicon, and potential controls on nutrient stoichiometry, across the land–ocean continuum in Great Britain - Andrew M. Tye; Helen P. Jarvie; Bryan M. Spears; Nancy B. Dise; Jennifer L. Williamson; Dan J. Lapworth; Don Monteith; Richard Sanders; Daniel J. Mayor; Michael J. Bowes; Michael Bowes; Annette Burden; et al. (Journal of Hydrology, 2024)

Influence of protein and leucine on in vitro accessibility and apparent permeability of phenolic compounds in blackberry-dairy blends - Tessa M. van de Langerijt; Yvonne C. O'Callaghan; Katerina Tzima; Conor C. Carey; Alice Lucey; Nora M. O'Brien; James A. O'Mahony; Dilip K. Rai; Shane V. Crowley (Food Bioscience, 2024)

Using social media records to inform conservation planning - Shawan Chowdhury; Richard A. Fuller; Sultan Ahmed; Shofiul Alam; Corey T. Callaghan; Priyanka Das; Ricardo A. Correia; Moreno Di Marco; Enrico Di Minin; Ivan Jarić; Mahzabin Muzahid Labi; Richard J. Ladle; et al. (Conservation Biology, 2024)
Citizen science plays a crucial role in helping monitor biodiversity and inform conservation. With the widespread use of smartphones, many people share biodiversity information on social media, but this information is still not widely used in conservation. Focusing on Bangladesh, a tropical megadiverse and mega‐populated country, we examined the importance of social media records in conservation decision‐making. We collated species distribution records for birds and butterflies from Facebook and Global Biodiversity Information Facility (GBIF), grouped them into GBIF‐only and combined GBIF and Facebook data, and investigated the differences in identifying critical conservation areas. Adding Facebook data to GBIF data improved the accuracy of systematic conservation planning assessments by identifying additional important conservation areas in the northwest, southeast, and central parts of Bangladesh, extending priority conservation areas by 4,000–10,000 km 2 . Community efforts are needed to drive the implementation of the ambitious Kunming–Montreal Global Biodiversity Framework targets, especially in megadiverse tropical countries with a lack of reliable and up‐to‐date species distribution data. We highlight that conservation planning can be enhanced by including available data gathered from social media platforms.

Relative quantitative proteomic profiling of bovine colostrum and transition milk at onset of lactation - Hannah K. Masterson; Tom F. O'Callaghan; Michael O'Donovan; John Paul Murphy; Katie Sugrue; Rebecca A. Owens; Rita M. Hickey (International Dairy Journal, 2024)

Attention, sentiments and emotions towards emerging climate technologies on Twitter - Finn Müller-Hansen; Tim Repke; Chad M. Baum; Elina Brutschin; Max W. Callaghan; Ramit Debnath; William F. Lamb; Sean Low; Sarah Lück; Cameron Roberts; Benjamin K. Sovacool; Jan C. Minx (Global Environmental Change, 2023)

Logistical considerations and challenges in deploying virtual biomethane pipelines to serve on-farm biogas plants - Dónal Ó Céileachair; Seán O'Callaghan; David M. Wall; David Goulding; Declan O'Connor; Jerry D. Murphy; Richard O'Shea (Journal of Cleaner Production, 2023)

Citizen science participant motivations and behaviour: Implications for biodiversity data coverage - Maureen M. Thompson; Katie Moon; Adam Woods; Jodi J.L. Rowley; Alistair G.B. Poore; Richard T. Kingsford; Corey T. Callaghan (Biological Conservation, 2023)

From COVID-19 to Green Recovery with natural capital accounting - Michael Vardon; Paul Lucas; Steve Bass; Matthew Agarwala; Andrea M. Bassi; Diane Coyle; Anthony Dvarskas; Catherine A. Farrell; Oliver Greenfield; Steven King; Martin Lok; Carl Obst; et al. (Ambio, 2023)
The COVID-19 pandemic and related social and economic emergencies induced massive public spending and increased global debt. Economic recovery is now an opportunity to rebuild natural capital alongside financial, physical, social and human capital, for long-term societal benefit. Yet, current decision-making is dominated by economic imperatives and information systems that do not consider society’s dependence on natural capital and the ecosystem services it provides. New international standards for natural capital accounting (NCA) are now available to integrate environmental information into government decision-making. By revealing the effects of policies that influence natural capital, NCA supports identification, implementation and monitoring of Green Recovery pathways, including where environment and economy are most positively interlinked.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Impacts of environmental change on biodiversity and vegetation dynamics in Siberia - Sergey N. Kirpotin; Terry V. Callaghan; Anna M. Peregon; Andrei S. Babenko; Daniil I. Berman; Nina A. Bulakhova; Arysia A. Byzaakay; Tatiana M. Chernykh; Vladislav Chursin; Elena A. Interesova; Sergey P. Gureev; Ivan A. Kerchev; et al. (Ambio, 2021)

Phenotypic plasticity as a cause and consequence of population dynamics - Dominic P. Brass; Christina A. Cobbold; David A. Ewing; Bethan V. Purse; Amanda Callaghan; Steven M. White (Ecology Letters, 2021)
Predicting complex species‐environment interactions is crucial for guiding conservation and mitigation strategies in a dynamically changing world. Phenotypic plasticity is a mechanism of trait variation that determines how individuals and populations adapt to changing and novel environments. For individuals, the effects of phenotypic plasticity can be quantified by measuring environment–trait relationships, but it is often difficult to predict how phenotypic plasticity affects populations. The assumption that environment–trait relationships validated for individuals indicate how populations respond to environmental change is commonly made without sufficient justification. Here we derive a novel general mathematical framework linking trait variation due to phenotypic plasticity to population dynamics. Applying the framework to the classical example of Nicholson's blowflies, we show how seemingly sensible predictions made from environment–trait relationships do not generalise to population responses. As a consequence, trait‐based analyses that do not incorporate population feedbacks risk mischaracterising the effect of environmental change on populations.

An ecological baseline for Laminaria hyperborea forests in western Ireland - Kathryn M. Schoenrock; Rory O'Callaghan; Tony O'Callaghan; Aisha O'Connor; Dagmar B. Stengel (Limnology and Oceanography, 2021)
The biodiversity associated with subtidal Irish kelp forests dominated by Laminaria hyperborea has never been described. To enumerate species assemblages in these ecosystems, subtidal surveys were done throughout the calendar year to investigate species assemblages within kelp forests, composition of benthic communities, species colonizing kelp thalli, recruitment to kelp forests, and habitat recovery processes after canopy clearances. Surveys were further undertaken in maërl beds, sediment‐bottom bays, Serpula vermicularis reefs, and bedrock habitats for comparison. Across all four seasons, kelp forests harbor the richest species assemblages, second only S. vermicularis reefs in diversity, with a total of 313 unique species in the habitat (from juvenile recruits to mature macrofauna). Peak diversity in kelp forests occurred in summer and echinoderms were one of the most abundant groups, though urchins never reach densities that would threaten over‐grazing. The thalli of L. hyperborea are diverse habitats harboring many deposit feeders, filter feeders, and marine macroalgae. Epibiotic communities become more diverse with age of kelp, culminating in a maximum of 1660 individuals on stipes and 949 on holdfasts. Recruitment of crustaceans, echinoderms, and worms was high in kelp forests, but recruitment of common Irish fish could not be monitored because of unique life history stage. Habitat establishment took over a year on artificial substrata which were colonized by macroalgae and dense canopy cover inhibited growth of juvenile sporophytes. This descriptive study represents an essential baseline for kelp forest biodiversity in Ireland.

Thermal flexibility and a generalist life history promote urban affinity in butterflies - Corey T. Callaghan; Diana E. Bowler; Henrique M. Pereira (Global Change Biology, 2021)
Urban expansion poses a serious threat to biodiversity. Given that the expected area of urban land cover is predicted to increase by 2–3 million km 2 by 2050, urban environments are one of the most widespread human‐dominated land‐uses affecting biodiversity. Responses to urbanization differ greatly among species. Some species are unable to tolerate urban environments (i.e., urban avoiders), others are able to adapt and use areas with moderate levels of urbanization (i.e., urban adapters), and yet others are able to colonize and even thrive in urban environments (i.e., urban exploiters). Quantifying species‐specific responses to urbanization remains an important goal, but our current understanding of urban tolerance is heavily biased toward traditionally well‐studied taxa (e.g., mammals and birds). We integrated a continuous measure of urbanization—night‐time lights—with over 900,000 species' observations from the Global Biodiversity Information Facility to derive a comprehensive analysis of species‐specific ( N = 158 species) responses of butterflies to urbanization across Europe. The majority of butterfly species included in our analysis avoided urban areas, regardless of whether species' urban affinities were quantified as a mean score of urban affinity across all occurrences (79%) or as a species' response curve to the whole urbanization gradient (55%). We then used species‐specific responses to urbanization to assess which life history strategies promote urban affinity in butterflies. These trait‐based analyses found strong evidence that the average number of flight months, likely associated with thermal niche breath, and number of adult food types were positively associated with urban affinity, while hostplant specialism was negatively associated with urban affinity. Overall, our results demonstrate that specialist butterflies, both in terms of thermal and diet preferences, are most at risk from increasing urbanization, and should thus be considered in urban planning and prioritized for conservation.

Mechanisms of Lateral Spreading in a Near-Field Buoyant River Plume Entering a Fjord - Rebecca A. McPherson; Craig L. Stevens; Joanne M. O'Callaghan; Andrew J. Lucas; Jonathan D. Nash (Frontiers in Marine Science, 2021)
Observations collected from a fast-flowing buoyant river plume entering the head of Doubtful Sound, New Zealand, were analysed to examine the drivers of plume lateral spreading. The near-field plume is characterised by flow speeds of over 2 ms −1 , and strong stratification ( N 2 > 0.1 s −2 ), resulting in enhanced shear which supports the elevated turbulence dissipation rates (ϵ > 10 −3 W kg −1 ). Estimates of plume lateral spreading rates were derived from the trajectories of Lagrangian GPS surface drifters and from cross-plume hydrographic transects. Lateral spreading rates derived from the latter compared favourably with estimates derived from a control volume technique in a previous study. The lateral spreading of the plume was driven by a baroclinic pressure gradient toward the base of the plume. However, spreading rates were underestimated by the surface drifters. A convergence of near-surface flow from the barotropic pressure gradient concentrated the drifters within the plume core. The combination of enhanced internal turbulence stress and mixing at the base of the surface layer, and the presence of steep fjord sidewalls likely reduced the rate of lateral spreading relative to the theoretical spreading rate. The estimates of plume width from the observations provided evidence of scale-dependent dispersion which followed a 4/3 power law. Two theoretical models of dispersion, turbulence and shear flow dispersion, were examined to assess which was capable of representing the observed spreading. An analytical horizontal shear-flow dispersion model generated estimates of lateral dispersion that were consistent with the observed 4/3 law of dispersion. Therefore, horizontal shear dispersion appeared to be the dominant mechanism of dispersion, thus spreading, in the surface plume layer.

Corrigendum: OceanGliders: A Component of the Integrated GOOS - Pierre Testor; Brad de Young; Daniel L. Rudnick; Scott Glenn; Daniel Hayes; Craig M. Lee; Charitha Pattiaratchi; Katherine Hill; Emma Heslop; Victor Turpin; Pekka Alenius; Carlos Barrera; et al. (Frontiers in Marine Science, 2021)

Long‐term trends in the frequency and magnitude of upwelling along the West Coast of the South Island, New Zealand, and the impact on primary production - Stephen M. Chiswell; Joanne M. O’Callaghan (New Zealand Journal of Marine and Freshwater Research, 2021)
Satellite‐derived estimates of sea surface temperature (SST), chlorophyll (Chl), and fluorescence line height (FLH), from 22 sites ∼20 km offshore from the West Coast of the South Island, New Zealand (WCSI) are used to investigate long‐term trends in SST, the frequency and magnitude of cool and warm events, and their impacts on SSC and FLH. WCSI trends have been towards higher temperature and less chlorophyll, with a 0.83°C rise in mean along‐shore SST since 1982, and a 0.1 mg Chl m −3 drop in mean along‐shore SSC since 2002. With respect to the trend, there were 13 extreme cool and 14 extreme warm events between 1982 and 2019, with mean values of −2.55 and 2.62°C, respectively. There was no measurable change in the frequency of extreme events, but there is a suggestion that extreme events are becoming warmer. During extreme events, Chl and FLH show inverse relationships with SST, suggesting that there is an underlying response of increased primary production to lower temperatures. Likely mechanisms are that upwelling brings nutrients up from depth, or that Ekman flow forces freshwater farther offshore, simultaneously introducing nutrients into the offshore region and providing a more stable water column allowing production.

The physics of New Zealand’s shelf seas: introduction to the special issue - Craig L. Stevens; Joe O’Callaghan; Stephen M. Chiswell; Moninya Roughan (New Zealand Journal of Marine and Freshwater Research, 2021)

Physical oceanography of New Zealand/Aotearoa shelf seas – a review - Craig L. Stevens; Joanne M. O’Callaghan; Stephen M. Chiswell; Mark G. Hadfield (New Zealand Journal of Marine and Freshwater Research, 2021)
The shelf seas surrounding New Zealand/Aotearoa, a region nominally extending out to the 250 m depth contour, are complex and varied as they sit above the submerged continent of Zealandia. These seas surround the two main islands that span 1,500 km in latitude from 34°S to 47°S and include a series of plateaus that extend far beyond. This review summarises the present state of knowledge of the physical processes that control ocean transport and mixing in this domain. The focus is on documenting recent regional advances in understanding the balance between off‐shelf drivers, terrestrially sourced freshwater, winds, tides, stratification and the underlying topography. The review considers outstanding themes such as connectivity, climate and stratification and closes with an assessment of the potential future for understanding the physical marine environment of the shelf seas of the New Zealand region.

Seagrass losses since mid‐20th century fuelled CO 2 emissions from soil carbon stocks - Cristian Salinas; Carlos M. Duarte; Paul S. Lavery; Pere Masque; Ariane Arias‐Ortiz; Javier X. Leon; David Callaghan; Gary A. Kendrick; Oscar Serrano (Global Change Biology, 2020)
Seagrass meadows store globally significant organic carbon (C org ) stocks which, if disturbed, can lead to CO 2 emissions, contributing to climate change. Eutrophication and thermal stress continue to be a major cause of seagrass decline worldwide, but the associated CO 2 emissions remain poorly understood. This study presents comprehensive estimates of seagrass soil C org erosion following eutrophication‐driven seagrass loss in Cockburn Sound (23 km 2 between 1960s and 1990s) and identifies the main drivers. We estimate that shallow seagrass meadows ( org stocks in 50 cm thick soils (4.5 ± 0.7 kg C org /m 2 ) than previously vegetated counterparts (0.5 ± 0.1 kg C org /m 2 ). In deeper areas (>5 m), however, soil C org stocks in seagrass and bare but previously vegetated areas were not significantly different (2.6 ± 0.3 and 3.0 ± 0.6 kg C org /m 2 , respectively). The soil C org sequestration capacity prevailed in shallow and deep vegetated areas (55 ± 11 and 21 ± 7 g C org m −2 year −1 , respectively), but was lost in bare areas. We identified that seagrass canopy loss alone does not necessarily drive changes in soil C org but, when combined with high hydrodynamic energy, significant erosion occurred. Our estimates point at ~0.20 m/s as the critical shear velocity threshold causing soil C org erosion. We estimate, from field studies and satellite imagery, that soil C org erosion (within the top 50 cm) following seagrass loss likely resulted in cumulative emissions of 0.06–0.14 Tg CO 2‐eq over the last 40 years in Cockburn Sound. We estimated that indirect impacts (i.e. eutrophication, thermal stress and light stress) causing the loss of ~161,150 ha of seagrasses in Australia, likely resulted in the release of 11–21 Tg CO 2 ‐eq since the 1950s, increasing cumulative CO 2 emissions from land‐use change in Australia by 1.1%–2.3% per annum. The patterns described serve as a baseline to estimate potential CO 2 emissions following disturbance of seagrass meadows.

Habitat maps to enhance monitoring and management of the Great Barrier Reef - Chris M. Roelfsema; Eva M. Kovacs; Juan Carlos Ortiz; David P. Callaghan; Karlo Hock; Mathieu Mongin; Kasper Johansen; Peter J. Mumby; Magnus Wettle; Mike Ronan; Petra Lundgren; Emma V. Kennedy; et al. (Coral Reefs, 2020)

The role of turbulence and internal waves in the structure and evolution of a near-field river plume - Rebecca A. McPherson; Craig L. Stevens; Joanne M. O'Callaghan; Andrew J. Lucas; Jonathan D. Nash (Ocean Science, 2020)
An along-channel momentum budget is quantified in the near-field plume region of a controlled river flow entering Doubtful Sound, New Zealand. Observations include highly resolved density, velocity and turbulence, enabling a momentum budget to be constructed over a control volume. Estimates of internal stress (τ) were made from direct measurements of turbulence dissipation rates (ϵ) using vertical microstructure profiles. High flow speeds of the surface plume over 2 m s−1 and strong stratification (N2∼10-1 s−2) resulted in enhanced turbulence dissipation rates (ϵ>10-3 W kg−1) and internal stress (τ>10-2 m2 s−2) at the base of the surface layer. Internal waves were observed propagating along the base of the plume, potentially released subsequent to a hydraulic jump in the initial 1 km downstream of the plume discharge point. The momentum flux divergence of these internal waves suggests that almost 15 % of the total plume momentum can be transported out of the system by wave radiation, therefore playing a crucial role in the redistribution of momentum within the near-field plume. Observations illustrate that the evolution of the momentum budget components vary between the distinct surface plume layer and the turbulent, shear-stratified interfacial layer. Within the surface plume, a momentum balance was achieved. The dynamical balance demonstrates that the deceleration of the plume, driven by along-channel advection, is controlled by turbulence stress from the plume discharge point to as far as 3 km downstream. In the interfacial layer, however, the momentum equation was dominated by the turbulence stress term and the balance was not closed. The redistribution of momentum within the shear-stratified layer by internal wave radiation and other hydraulic features could account for the discrepancy in the budget.

Quantitation and chemical coding of enteroendocrine cell populations in the human jejunum - Therese E Fazio Coles; Linda J Fothergill; Billie Hunne; Mehrdad Nikfarjam; Adam Testro; Brid Callaghan; Rachel M McQuade; John B Furness (Cell and Tissue Research, 2020)

OceanGliders: A Component of the Integrated GOOS - Pierre Testor; Brad de Young; Daniel L. Rudnick; Scott Glenn; Daniel Hayes; Craig M. Lee; Charitha Pattiaratchi; Katherine Hill; Emma Heslop; Victor Turpin; Pekka Alenius; Carlos Barrera; et al. (Frontiers in Marine Science, 2019)
The OceanGliders program started in 2016 to support active coordination and enhancement of global glider activity. OceanGliders contributes to the international efforts of the Global Ocean Observation System (GOOS) for Climate, Ocean Health, and Operational Services. It brings together marine scientists and engineers operating gliders around the world: (1) to observe the long-term physical, biogeochemical, and biological ocean processes and phenomena that are relevant for societal applications; and, (2) to contribute to the GOOS through real-time and delayed mode data dissemination. The OceanGliders program is distributed across national and regional observing systems and significantly contributes to integrated, multi-scale and multi-platform sampling strategies. OceanGliders shares best practices, requirements, and scientific knowledge needed for glider operations, data collection and analysis. It also monitors global glider activity and supports the dissemination of glider data through regional and global databases, in real-time and delayed modes, facilitating data access to the wider community. OceanGliders currently supports national, regional and global initiatives to maintain and expand the capabilities and application of gliders to meet key global challenges such as improved measurement of ocean boundary currents, water transformation and storm forecast.

Relationships of endocrine cells to each other and to other cell types in the human gastric fundus and corpus - Josiane Fakhry; Martin J. Stebbing; Billie Hunne; Yulia Bayguinov; Sean M. Ward; Kent C. Sasse; Brid Callaghan; Rachel M. McQuade; John B. Furness (Cell and Tissue Research, 2019)

Regulation of biosimilar medicines and current perspectives on interchangeability and policy - J. O’Callaghan; S. P. Barry; M. Bermingham; J. M. Morris; B. T. Griffin (European Journal of Clinical Pharmacology, 2019)

Extreme drought pushes stream invertebrate communities over functional thresholds - Thomas W. H. Aspin; Kieran Khamis; Thomas J. Matthews; Alexander M. Milner; Matthew J. O’Callaghan; Mark Trimmer; Guy Woodward; Mark E. Ledger (Global Change Biology, 2019)
Functional traits are increasingly being used to predict extinction risks and range shifts under long‐term climate change scenarios, but have rarely been used to study vulnerability to extreme climatic events, such as supraseasonal droughts. In streams, drought intensification can cross thresholds of habitat loss, where marginal changes in environmental conditions trigger disproportionate biotic responses. However, these thresholds have been studied only from a structural perspective, and the existence of functional nonlinearity remains unknown. We explored trends in invertebrate community functional traits along a gradient of drought intensity, simulated over 18 months, using mesocosms analogous to lowland headwater streams. We modelled the responses of 16 traits based on a priori predictions of trait filtering by drought, and also examined the responses of trait profile groups (TPGs) identified via hierarchical cluster analysis. As responses to drought intensification were both linear and nonlinear, generalized additive models (GAMs) were chosen to model response curves, with the slopes of fitted splines used to detect functional thresholds during drought. Drought triggered significant responses in 12 (75%) of the a priori‐selected traits. Behavioural traits describing movement (dispersal, locomotion) and diet were sensitive to moderate‐intensity drought, as channels fragmented into isolated pools. By comparison, morphological and physiological traits showed little response until surface water was lost, at which point we observed sudden shifts in body size, respiration mode and thermal tolerance. Responses varied widely among TPGs, ranging from population collapses of non‐aerial dispersers as channels fragmented to irruptions of small, eurythermic dietary generalists upon extreme dewatering. Our study demonstrates for the first time that relatively small changes in drought intensity can trigger disproportionately large functional shifts in stream communities, suggesting that traits‐based approaches could be particularly useful for diagnosing catastrophic ecological responses to global change.

Somatic mutations of the coding microsatellites within the beta-2-microglobulin gene in mismatch repair-deficient colorectal cancers and adenomas - Mark Clendenning; Alvin Huang; Harindra Jayasekara; Marie Lorans; Susan Preston; Neil O’Callaghan; Bernard J. Pope; Finlay A. Macrae; Ingrid M. Winship; Roger L. Milne; Graham G. Giles; Dallas R. English; et al. (Familial Cancer, 2018)

Evaluating the Surface Response of Discharge Events in a New Zealand Gulf-ROFI - Joanne M. Ø'Callaghan; Craig L. Stevens (Frontiers in Marine Science, 2017)

Long-term P fertilisation of pasture soil did not increase soil organic matter stocks but increased microbial biomass and activity - S.A. Wakelin; L.M. Condron; E. Gerard; B.E.A. Dignam; A. Black; M. O’Callaghan (Biology and Fertility of Soils, 2017)

The short‐lived neon damsel Pomacentrus coelestis : implications for population dynamics - M. J. Kingsford; M. D. O'Callaghan; L. Liggins; G. Gerlach (Journal of Fish Biology, 2017)
Daily increments of Pomacentrus coelestis , an abundant and well‐studied fish, were validated for the life of the fish and depending on the location, age‐maxima were estimated to be 127–160 days on reefs separated by tens to hundreds of kilometres on the Great Barrier Reef. This contrasts with congeners and other damselfishes that live for 5 years or more. Otoliths of P. coelestis were thinner and had different patterns of banding when compared with relatively long‐lived congeners. It is suggested that banding patterns in P. coelestis may be related to patterns of maturation and spawning. The consequences of a short life would have a great influence on the population dynamics of this widespread species. Further, the demographics and habitat preferences of this species suggest rapid colonization and establishment of breeding populations that would quickly change the relative abundance of sympatric fishes.

Methanogenic paraffin degradation proceeds via alkane addition to fumarate by ‘Smithella’ spp. mediated by a syntrophic coupling with hydrogenotrophic methanogens - Boris Wawrik; Christopher R. Marks; Irene A. Davidova; Michael J. McInerney; Shane Pruitt; Kathleen E. Duncan; Joseph M. Suflita; Amy V. Callaghan (Environmental Microbiology, 2016)
Summary Anaerobic microbial biodegradation of recalcitrant, water‐insoluble substrates, such as paraffins, presents unique metabolic challenges. To elucidate this process, a methanogenic consortium capable of mineralizing long‐chain n ‐paraffins (C 28 ‐C 50 ) was enriched from San Diego Bay sediment. Analysis of 16S rRNA genes indicated the dominance of Syntrophobacterales (43%) and Methanomicrobiales (26%). Metagenomic sequencing allowed draft genome assembly of dominant uncultivated community members belonging to the bacterial genus Smithella and the archaeal genera Methanoculleus and Methanosaeta . Five contigs encoding homologs of the catalytic subunit of alkylsuccinate synthase ( assA ) were detected. Additionally, mRNA transcripts for these genes, including a homolog binned within the ‘ Smithella’ sp. SDB genome scaffold, were detected via RT‐PCR, implying that paraffins are activated via ‘fumarate addition’. Metabolic reconstruction and comparison with genome scaffolds of uncultivated n ‐alkane degrading ‘ Smithella’ spp. are consistent with the hypothesis that syntrophically growing ‘ Smithella’ spp. may achieve reverse electron transfer by coupling the reoxidation of ETF red to a membrane‐bound FeS oxidoreductase functioning as an ETF:menaquinone oxidoreductase. Subsequent electron transfer could proceed via a periplasmic formate dehydrogenase and/or hydrogenase, allowing energetic coupling to hydrogenotrophic methanogens such as Methanoculleus . Ultimately, these data provide fundamental insight into the energy conservation mechanisms that dictate interspecies interactions salient to methanogenic alkane mineralization.

The chemical coding of 5-hydroxytryptamine containing enteroendocrine cells in the mouse gastrointestinal tract - Yohan Reynaud; Josiane Fakhry; Linda Fothergill; Brid Callaghan; Mitchell Ringuet; Billie Hunne; David M. Bravo; John B. Furness (Cell and Tissue Research, 2016)

Cost of root disease on white clover growth in New Zealand dairy pastures - S.A. Wakelin; Y. Eslami; K. Dake; B.E.A. Dignam; M. O’Callaghan (Australasian Plant Pathology, 2016)

Nutrient- and sediment-induced macroinvertebrate drift in Honduran cloud forest streams - P. O’Callaghan; M. Jocqué; M. Kelly-Quinn (Hydrobiologia, 2015)

Effects of climate change on the delivery of soil‐mediated ecosystem services within the primary sector in temperate ecosystems: a review and New Zealand case study - Kate H. Orwin; Bryan A. Stevenson; Simeon J. Smaill; Miko U. F. Kirschbaum; Ian A. Dickie; Brent E. Clothier; Loretta G. Garrett; Tony J. van der Weerden; Michael H. Beare; Denis Curtin; Cecile A. M. de Klein; Michael B. Dodd; et al. (Global Change Biology, 2015)
Future human well‐being under climate change depends on the ongoing delivery of food, fibre and wood from the land‐based primary sector. The ability to deliver these provisioning services depends on soil‐based ecosystem services (e.g. carbon, nutrient and water cycling and storage), yet we lack an in‐depth understanding of the likely response of soil‐based ecosystem services to climate change. We review the current knowledge on this topic for temperate ecosystems, focusing on mechanisms that are likely to underpin differences in climate change responses between four primary sector systems: cropping, intensive grazing, extensive grazing and plantation forestry. We then illustrate how our findings can be applied to assess service delivery under climate change in a specific region, using New Zealand as an example system. Differences in the climate change responses of carbon and nutrient‐related services between systems will largely be driven by whether they are reliant on externally added or internally cycled nutrients, the extent to which plant communities could influence responses, and variation in vulnerability to erosion. The ability of soils to regulate water under climate change will mostly be driven by changes in rainfall, but can be influenced by different primary sector systems' vulnerability to soil water repellency and differences in evapotranspiration rates. These changes in regulating services resulted in different potentials for increased biomass production across systems, with intensively managed systems being the most likely to benefit from climate change. Quantitative prediction of net effects of climate change on soil ecosystem services remains a challenge, in part due to knowledge gaps, but also due to the complex interactions between different aspects of climate change. Despite this challenge, it is critical to gain the information required to make such predictions as robust as possible given the fundamental role of soils in supporting human well‐being.

Investigation of the multifaceted iron acquisition strategies of Burkholderia cenocepacia - J. Tyrrell; N. Whelan; C. Wright; I. Sá-Correia; S. McClean; M. Thomas; Máire Callaghan (BioMetals, 2015)

Differences in hormone localisation patterns of K and L type enteroendocrine cells in the mouse and pig small intestine and colon - Hyun-Jung Cho; Samin Kosari; Billie Hunne; Brid Callaghan; Leni R. Rivera; David M. Bravo; John B. Furness (Cell and Tissue Research, 2015)

Identification of enteroendocrine cells that express TRPA1 channels in the mouse intestine - Hyun-Jung Cho; Brid Callaghan; Romke Bron; David M. Bravo; John B. Furness (Cell and Tissue Research, 2014)

Correlation of Hemodynamic Parameters to Endothelial Cell Proliferation in an End to Side Anastomosis - Leonard D. Browne; Siobhan O’Callaghan; David A. Hoey; Philip Griffin; Timothy M. McGloughlin; Michael T. Walsh (Cardiovascular Engineering and Technology, 2014)

Planktonic Larval Duration, age and growth of Ostorhinchus doederleini (Pisces: Apogonidae) on the southern Great Barrier Reef, Australia - M. J. Kingsford; M. D. Finn; M. D. O’Callaghan; J. Atema; G. Gerlach (Marine Biology, 2014)

A geospatial assessment of the relationship between reef flat community calcium carbonate production and wave energy - S. M. Hamylton; A. Pescud; J. X. Leon; D. P. Callaghan (Coral Reefs, 2013)

Towards a unified paradigm for sequence‐based identification of fungi - Urmas Kõljalg; R. Henrik Nilsson; Kessy Abarenkov; Leho Tedersoo; Andy F. S. Taylor; Mohammad Bahram; Scott T. Bates; Thomas D. Bruns; Johan Bengtsson‐Palme; Tony M. Callaghan; Brian Douglas; Tiia Drenkhan; et al. (Molecular Ecology, 2013)
The nuclear ribosomal internal transcribed spacer ( ITS ) region is the formal fungal barcode and in most cases the marker of choice for the exploration of fungal diversity in environmental samples. Two problems are particularly acute in the pursuit of satisfactory taxonomic assignment of newly generated ITS sequences: (i) the lack of an inclusive, reliable public reference data set and (ii) the lack of means to refer to fungal species, for which no Latin name is available in a standardized stable way. Here, we report on progress in these regards through further development of the UNITE database ( http://unite.ut.ee ) for molecular identification of fungi. All fungal species represented by at least two ITS sequences in the international nucleotide sequence databases are now given a unique, stable name of the accession number type (e.g. H ymenoscyphus pseudoalbidus | GU 586904| SH 133781.05 FU ), and their taxonomic and ecological annotations were corrected as far as possible through a distributed, third‐party annotation effort. We introduce the term ‘species hypothesis’ ( SH ) for the taxa discovered in clustering on different similarity thresholds (97–99%). An automatically or manually designated sequence is chosen to represent each such SH. These reference sequences are released ( http://unite.ut.ee/repository.php ) for use by the scientific community in, for example, local sequence similarity searches and in the QIIME pipeline. The system and the data will be updated automatically as the number of public fungal ITS sequences grows. We invite everybody in the position to improve the annotation or metadata associated with their particular fungal lineages of expertise to do so through the new Web‐based sequence management system in UNITE .

The effect of partial outlet obstruction on calpain and phospholipase-2 activities: analyzed by severity and duration - Connor M. Callaghan; Arnold Johnson; Paul Neumann; Robert E. Leggett; Catherine Schuler; Robert M. Levin (Molecular and Cellular Biochemistry, 2013)

Coastal retreat and improved water quality mitigate losses of seagrass from sea level rise - Megan I. Saunders; Javier Leon; Stuart R. Phinn; David P. Callaghan; Katherine R. O'Brien; Chris M. Roelfsema; Catherine E. Lovelock; Mitchell B. Lyons; Peter J. Mumby (Global Change Biology, 2013)
The distribution and abundance of seagrass ecosystems could change significantly over the coming century due to sea level rise ( SLR ). Coastal managers require mechanistic understanding of the processes affecting seagrass response to SLR to maximize their conservation and associated provision of ecosystem services. In Moreton Bay, Queensland, Australia, vast seagrass meadows supporting populations of sea turtles and dugongs are juxtaposed with the multiple stressors associated with a large and rapidly expanding human population. Here, the interactive effects of predicted SLR , changes in water clarity, and land use on future distributions of seagrass in Moreton Bay were quantified. A habitat distribution model of present day seagrass in relation to benthic irradiance and wave height was developed which correctly classified habitats in 83% of cases. Spatial predictions of seagrass and presence derived from the model and bathymetric data were used to initiate a SLR inundation model. Bathymetry was iteratively modified based on SLR and sedimentary accretion in seagrass to simulate potential seagrass habitat at 10 year time steps until 2100. The area of seagrass habitat was predicted to decline by 17% by 2100 under a scenario of SLR of 1.1 m. A scenario including the removal of impervious surfaces, such as roads and houses, from newly inundated regions, demonstrated that managed retreat of the shoreline could potentially reduce the overall decline in seagrass habitat to just 5%. The predicted reduction in area of seagrass habitat could be offset by an improvement in water clarity of 30%. Greater improvements in water clarity would be necessary for larger magnitudes of SLR . Management to improve water quality will provide present and future benefits to seagrasses under climate change and should be a priority for managers seeking to compensate for the effects of global change on these valuable habitats.

A Design Space Verification Protocol for a Small Molecule Drug Substance - Timothy J. N. Watson; Holly Bonsignore; Eileen A. Callaghan-Manning; Stephen T. Colgan; Paul Fitzsimons; Thomas P. Garcia; John G. Groskoph; Michael P. Lynch; Roger Nosal; Megan E. McMahon; Robert A. Singer; Nicholas M. Thomson; et al. (Journal of Pharmaceutical Innovation, 2013)

Effect of 7-year application of a nitrification inhibitor, dicyandiamide (DCD), on soil microbial biomass, protease and deaminase activities, and the abundance of bacteria and archaea in pasture soils - Yan J. Guo; Hong J. Di; Keith C. Cameron; Bowen Li; Andriy Podolyan; Jim L. Moir; Ross M. Monaghan; L. Chris Smith; Maureen O’Callaghan; Saman Bowatte; Deanne Waugh; Ji-Zheng He (Journal of Soils and Sediments, 2013)

CCL27–CCR10 and CXCL12–CXCR4 chemokine ligand-receptor mRNA expression ratio: new predictive factors of tumor progression in cutaneous malignant melanoma - Carlos Monteagudo; David Ramos; Ana Pellín-Carcelén; Rosario Gil; Robert C. Callaghan; José M. Martín; Vicent Alonso; Amelia Murgui; Lara Navarro; Silvia Calabuig; José Antonio López-Guerrero; Esperanza Jordá; et al. (Clinical & Experimental Metastasis, 2012)

Abundance patterns of cubozoans on and near the Great Barrier Reef - M. J. Kingsford; J. E. Seymour; M. D. O’Callaghan (Hydrobiologia, 2012)

Changes Versus Homeostasis in Alpine and Sub-Alpine Vegetation Over Three Decades in the Sub-Arctic - Henrik Hedenås; Bengt Å. Carlsson; Urban Emanuelsson; Alistair D. Headley; Christer Jonasson; Brita M. Svensson; Terry V. Callaghan (Ambio, 2012)

Mild Clinical and Biochemical Phenotype in Two Patients with PMM2-CDG (Congenital Disorder of Glycosylation Ia) - M. Casado; M. M. O’Callaghan; R. Montero; C. Pérez-Cerda; B. Pérez; P. Briones; E. Quintana; J. Muchart; A. Aracil; M. Pineda; R. Artuch (The Cerebellum, 2012)

Adoption of variable rate fertiliser application in the Australian grains industry: status, issues and prospects - M. J. Robertson; R. S. Llewellyn; R. Mandel; R. Lawes; R. G. V. Bramley; L. Swift; N. Metz; C. O’Callaghan (Precision Agriculture, 2012)

Extreme winter warming events more negatively impact small rather than large soil fauna: shift in community composition explained by traits not taxa - S. Bokhorst; G. K. Phoenix; J. W. Bjerke; T. V. Callaghan; F. Huyer‐Brugman; M. P. Berg (Global Change Biology, 2012)
Extreme weather events can have negative impacts on species survival and community structure when surpassing lethal thresholds. Extreme winter warming events in the A rctic rapidly melt snow and expose ecosystems to unseasonably warm air (2–10 °C for 2–14 days), but returning to cold winter climate exposes the ecosystem to lower temperatures by the loss of insulating snow. Soil animals, which play an integral part in soil processes, may be very susceptible to such events depending on the intensity of soil warming and low temperatures following these events. We simulated week‐long extreme winter warming events – using infrared heating lamps, alone or with soil warming cables – for two consecutive years in a sub‐ A rctic dwarf shrub heathland. Minimum temperatures were lower and freeze‐thaw cycles were 2–11 times more frequent in treatment plots compared with control plots. Following the second event, A cari populations decreased by 39%; primarily driven by declines of P rostigmata (69%) and the M esostigmatic nymphs (74%). A community‐weighted vertical stratification shift occurred from smaller soil dwelling (eu‐edaphic) C ollembola species dominance to larger litter dwelling (hemi‐edaphic) species dominance in the canopy‐with‐soil warming plots compared with controls. The most susceptible groups to these winter warming events were the smallest individuals ( P rostigmata and eu‐edaphic C ollembola). This was not apparent from abundance data at the C ollembola taxon level, indicating that life forms and species traits play a major role in community assembly following extreme events. The observed shift in soil community can cascade down to the micro‐flora affecting plant productivity and mineralization rates. Short‐term extreme weather events have the potential to shift community composition through trait composition with potentially large consequences for ecosystem development.

Global assessment of experimental climate warming on tundra vegetation: heterogeneity over space and time - Sarah C. Elmendorf; Gregory H. R. Henry; Robert D. Hollister; Robert G. Björk; Anne D. Bjorkman; Terry V. Callaghan; Laura Siegwart Collier; Elisabeth J. Cooper; Johannes H. C. Cornelissen; Thomas A. Day; Anna Maria Fosaa; William A. Gould; et al. (Ecology Letters, 2012)
Ecology Letters (2011) Abstract Understanding the sensitivity of tundra vegetation to climate warming is critical to forecasting future biodiversity and vegetation feedbacks to climate. In situ warming experiments accelerate climate change on a small scale to forecast responses of local plant communities. Limitations of this approach include the apparent site‐specificity of results and uncertainty about the power of short‐term studies to anticipate longer term change. We address these issues with a synthesis of 61 experimental warming studies, of up to 20 years duration, in tundra sites worldwide. The response of plant groups to warming often differed with ambient summer temperature, soil moisture and experimental duration. Shrubs increased with warming only where ambient temperature was high, whereas graminoids increased primarily in the coldest study sites. Linear increases in effect size over time were frequently observed. There was little indication of saturating or accelerating effects, as would be predicted if negative or positive vegetation feedbacks were common. These results indicate that tundra vegetation exhibits strong regional variation in response to warming, and that in vulnerable regions, cumulative effects of long‐term warming on tundra vegetation – and associated ecosystem consequences – have the potential to be much greater than we have observed to date.

The genome sequence of Desulfatibacillum alkenivorans AK‐01: a blueprint for anaerobic alkane oxidation - A. V. Callaghan; B. E. L. Morris; I. A. C. Pereira; M. J. McInerney; R. N. Austin; J. T. Groves; J. J. Kukor; J. M. Suflita; L. Y. Young; G. J. Zylstra; B. Wawrik (Environmental Microbiology, 2012)
Summary Desulfatibacillum alkenivorans AK‐01 serves as a model organism for anaerobic alkane biodegradation because of its distinctive biochemistry and metabolic versatility. The D. alkenivorans genome provides a blueprint for understanding the genetic systems involved in alkane metabolism including substrate activation, CoA ligation, carbon‐skeleton rearrangement and decarboxylation. Genomic analysis suggested a route to regenerate the fumarate needed for alkane activation via methylmalonyl‐CoA and predicted the capability for syntrophic alkane metabolism, which was experimentally verified. Pathways involved in the oxidation of alkanes, alcohols, organic acids and n ‐saturated fatty acids coupled to sulfate reduction and the ability to grow chemolithoautotrophically were predicted. A complement of genes for motility and oxygen detoxification suggests that D. alkenivorans may be physiologically adapted to a wide range of environmental conditions. The D. alkenivorans genome serves as a platform for further study of anaerobic, hydrocarbon‐oxidizing microorganisms and their roles in bioremediation, energy recovery and global carbon cycling.

Multiple Effects of Changes in Arctic Snow Cover - Terry V. Callaghan; Margareta Johansson; Ross D. Brown; Pavel Ya. Groisman; Niklas Labba; Vladimir Radionov; Raymond S. Bradley; Sylvie Blangy; Olga N. Bulygina; Torben R. Christensen; Jonathan E. Colman; Richard L. H. Essery; et al. (Ambio, 2011)

The Changing Arctic Cryosphere and Likely Consequences: An Overview - M. S. Olsen; T. V. Callaghan; J. D. Reist; L. O. Reiersen; D. Dahl-Jensen; M. A. Granskog; B. Goodison; G. K. Hovelsrud; M. Johansson; R. Kallenborn; J. Key; A. Klepikov; et al. (Ambio, 2011)

Ecological Implications of Changes in the Arctic Cryosphere - Warwick F. Vincent; Terry V. Callaghan; Dorthe Dahl-Jensen; Margareta Johansson; Kit M. Kovacs; Christine Michel; Terry Prowse; James D. Reist; Martin Sharp (Ambio, 2011)

The Changing Face of Arctic Snow Cover: A Synthesis of Observed and Projected Changes - Terry V. Callaghan; Margareta Johansson; Ross D. Brown; Pavel Ya. Groisman; Niklas Labba; Vladimir Radionov; Roger G. Barry; Olga N. Bulygina; Richard L. H. Essery; D. M. Frolov; Vladimir N. Golubev; Thomas C. Grenfell; et al. (Ambio, 2011)

Arctic Cryosphere: Changes and Impacts - T. V. Callaghan; M. Johansson; T. D. Prowse; M. S. Olsen; L.-O. Reiersen (Ambio, 2011)

Expression of Sex and Reproduction-Related Genes in Marsupenaeus japonicus - Tamera R. Callaghan; Bernard M. Degnan; Melony J. Sellars (Marine Biotechnology, 2010)

Hippuric acid and benzoic acid inhibition of urine derived N 2 O emissions from soil - JANET E. BERTRAM; TIM J. CLOUGH; ROBERT R. SHERLOCK; LEO M. CONDRON; MAUREEN O'CALLAGHAN; NAOMI S. WELLS; JESSICA L. RAY (Global Change Biology, 2009)
Atmospheric concentrations of the greenhouse gas nitrous oxide (N 2 O) have continued to rise since the advent of the industrial era, largely because of the increase in agricultural land use. The urine deposited by grazing ruminant animals is a major global source of agricultural N 2 O. With the first commitment period for reducing greenhouse gas emissions under the Kyoto Protocol now underway, mitigation options for ruminant urine N 2 O emissions are urgently needed. Recent studies showed that increasing the urinary concentration of the minor urine constituent hippuric acid resulted in reduced emissions of N 2 O from a sandy soil treated with synthetic bovine urine, due to a reduction in denitrification. A similar effect was seen when benzoic acid, a product of hippuric acid hydrolysis, was used. This current laboratory experiment aimed to investigate these effects using real cow urine for the first time. Increased concentrations of hippuric acid or benzoic acid in the urine led to reduction of N 2 O emissions by 65% (from 17% to 2 O fluxes. This study indicates the potential for developing a novel mitigation strategy based on manipulation of urine composition through ruminant diet.

The genomic basis of cerebral palsy: a HuGE systematic literature review - M. E. O’Callaghan; A. H. MacLennan; E. A. Haan; G. Dekker (Human Genetics, 2009)

Ecosystem responses to increased precipitation and permafrost decay in subarctic Sweden inferred from peat and lake sediments - U. KOKFELT; P. ROSÉN; K. SCHONING; T. R. CHRISTENSEN; J. FÖRSTER; J. KARLSSON; N. REUSS; M. RUNDGREN; T. V. CALLAGHAN; C. JONASSON; D. HAMMARLUND (Global Change Biology, 2009)
Recent accelerated decay of discontinuous permafrost at the Stordalen Mire in northern Sweden has been attributed to increased temperature and snow depth, and has caused expansion of wet minerotrophic areas leading to significant changes in carbon cycling in the mire. In order to track these changes through time and evaluate potential forcing mechanisms, this paper analyses a peat succession and a lake sediment sequence from within the mire, providing a record for the last 100 years, and compares these with monitored climate and active layer thickness data. The peat core was analysed for testate amoebae to reconstruct changes in peatland surface moisture conditions and water table fluctuations. The lake sediment core was analysed by near infrared spectroscopy to infer changes in the total organic carbon (TOC) concentration of the lake‐water, and changes in δ 13 C and C, N and δ 15 N to track changes in the dissolved inorganic carbon (DIC) pool and the influence of diagenetic effects on sediment organic matter, respectively. Results showed that major shifts towards increased peat surface moisture and TOC concentration of the lake‐water occurred around 1980, one to two decades earlier than a temperature driven increase in active layer thickness. Comparison with monitored temperature and precipitation from a nearby climate station indicates that this change in peat surface moisture is related to June–September (JJAS) precipitation and that the increase in lake‐water TOC concentration reflects an increase in total annual precipitation. A significant depletion in 13 C of sediment organic matter in the early 1980s probably reflects the effect of a single or a few consecutive years with anomalously high summer precipitation, resulting in elevated DIC content of the lake water, predominantly originating from increased export and subsequent respiration of organic carbon from the mire. Based on these results, it was not possible to link proxy data obtained on peat and lake‐sediment records directly to permafrost decay. Instead our data indicate that increased precipitation and anomalously high rainfall during summers had a significant impact on the mire and the adjacent lake ecosystem. We therefore propose that effects of increased precipitation should be considered when evaluating potential forcing mechanisms of recent changes in carbon cycling in the subarctic.

Elevated temperature restricts growth potential of the coral reef fish Acanthochromis polyacanthus - P. L. Munday; M. J. Kingsford; M. O’Callaghan; J. M. Donelson (Coral Reefs, 2008)

Plant species traits are the predominant control on litter decomposition rates within biomes worldwide - William K. Cornwell; Johannes H. C. Cornelissen; Kathryn Amatangelo; Ellen Dorrepaal; Valerie T. Eviner; Oscar Godoy; Sarah E. Hobbie; Bart Hoorens; Hiroko Kurokawa; Natalia Pérez‐Harguindeguy; Helen M. Quested; Louis S. Santiago; et al. (Ecology Letters, 2008)
Worldwide decomposition rates depend both on climate and the legacy of plant functional traits as litter quality. To quantify the degree to which functional differentiation among species affects their litter decomposition rates, we brought together leaf trait and litter mass loss data for 818 species from 66 decomposition experiments on six continents. We show that: (i) the magnitude of species‐driven differences is much larger than previously thought and greater than climate‐driven variation; (ii) the decomposability of a species’ litter is consistently correlated with that species’ ecological strategy within different ecosystems globally, representing a new connection between whole plant carbon strategy and biogeochemical cycling. This connection between plant strategies and decomposability is crucial for both understanding vegetation–soil feedbacks, and for improving forecasts of the global carbon cycle.

Complementing structural information of modular proteins with small angle neutron scattering and contrast variation - J. G. Grossmann; A. J. Callaghan; M. J. Marcaida; B. F. Luisi; F. H. Alcock; K. Tokatlidis; M. Moulin; M. Haertlein; P. Timmins (European Biophysics Journal, 2008)

Complementing structural information of modular proteins with small angle neutron scattering and contrast variation - J. G. Grossmann; A. J. Callaghan; M. J. Marcaida; B. F. Luisi; F. H. Alcock; K. Tokatlidis (European Biophysics Journal, 2008)

Reproduction recovery of the crustacean Daphnia magna after chronic exposure to ibuprofen - Yuya Hayashi; Lars-Henrik Heckmann; Amanda Callaghan; Richard M. Sibly (Ecotoxicology, 2008)

Role of lipase in Burkholderia cepacia complex (Bcc) invasion of lung epithelial cells - T. Mullen; K. Markey; P. Murphy; S. McClean; M. Callaghan (European Journal of Clinical Microbiology & Infectious Diseases, 2007)

A simple and rapid method for preserving RNA of aquatic invertebrates for ecotoxicogenomics - Lars-Henrik Heckmann; Anthony Bouetard; Christopher J. Hill; Richard M. Sibly; Amanda Callaghan (Ecotoxicology, 2007)

Global negative vegetation feedback to climate warming responses of leaf litter decomposition rates in cold biomes - Johannes H.C. Cornelissen; Peter M. Van Bodegom; Rien Aerts; Terry V. Callaghan; Richard S.P. Van Logtestijn; Juha Alatalo; F. Stuart Chapin; Renato Gerdol; Jon Gudmundsson; Dylan Gwynn‐Jones; Anne E. Hartley; David S. Hik; et al. (Ecology Letters, 2007)
Whether climate change will turn cold biomes from large long‐term carbon sinks into sources is hotly debated because of the great potential for ecosystem‐mediated feedbacks to global climate. Critical are the direction, magnitude and generality of climate responses of plant litter decomposition. Here, we present the first quantitative analysis of the major climate‐change‐related drivers of litter decomposition rates in cold northern biomes worldwide. Leaf litters collected from the predominant species in 33 global change manipulation experiments in circum‐arctic‐alpine ecosystems were incubated simultaneously in two contrasting arctic life zones. We demonstrate that longer‐term, large‐scale changes to leaf litter decomposition will be driven primarily by both direct warming effects and concomitant shifts in plant growth form composition, with a much smaller role for changes in litter quality within species. Specifically, the ongoing warming‐induced expansion of shrubs with recalcitrant leaf litter across cold biomes would constitute a negative feedback to global warming. Depending on the strength of other (previously reported) positive feedbacks of shrub expansion on soil carbon turnover, this may partly counteract direct warming enhancement of litter decomposition.

Effects of past and current crop management on soil microbial biomass and activity - Christine Stark; Leo M. Condron; Alison Stewart; Hong J. Di; Maureen O’Callaghan (Biology and Fertility of Soils, 2007)

Comparison of antibiotic susceptibility of Burkholderia cepacia complex organisms when grown planktonically or as biofilm in vitro - E. Caraher; G. Reynolds; P. Murphy; S. McClean; M. Callaghan (European Journal of Clinical Microbiology & Infectious Diseases, 2007)

A submersible device for measuring drag forces on aquatic plants and other organisms - Fraser M. Callaghan; Glenn G. Cooper; Vladimir I. Nikora; Nicolas Lamouroux; Bernhard Statzner; Pierre Sagnes; John Radford; Emmanuel Malet; Barry J.F. Biggs (New Zealand Journal of Marine and Freshwater Research, 2007)
This paper describes a device, the submersible drag gauge (SDG), that can be used for drag measurements in studies of flow‐biota interactions at low (setup A) and high (setup B) load applications. The device is designed so that solely drag forces acting on a test object in a boundary layer now are measured. The SDG can measure drag on organism(s), such as macrophtyes, crayfish or mussels, as well as a combination of such organisms and sediments assembled in a variety of arrangements in both laboratory and field conditions. Laboratory calibrations over the range of 0 to 4 N showed that setup A registered forces as low as 0.02 N, whereas setup B often did not register forces up to c. 0.15 N. The relative standard error of drag measurements was 0.2 N (setup A) or 1 N (setup B). Using a rigid cylinder, and natural and artificial (plastic) Egeria densa as examples, showed how the SDG can serve in studies of flow‐biota interactions such as drag‐velocity relations, assessments of drag coefficients, or the frequency spectrum of macrophyte drag.

Effects of flume characteristics on the assessment of drag on flexible macrophytes and a rigid cylinder - Glenn G. Cooper; Fraser M. CallaGhan; Vladimir I. Nikora; Nicolas Lamouroux; Bernhard Statzner; Pierre Sagnes (New Zealand Journal of Marine and Freshwater Research, 2007)
Previous research, using rigid objects, showed that the magnitude of mean drag on submerged bodies can be influenced by the blockage ratio (ratio of the frontal projection area of an object to the wetted flume cross‐sectional area). In addition, drag measurements, under similar flow conditions, are likely to be affected by other flume characteristics. these factors lead to some uncertainty in drag measurement comparisons between identical objects for a given reference flow velocity. We measured drag on three pairs of replicate objects (two types of flexible artificial macrophyte and a rigid cylinder) in two flumes differing in width (0.25 and 0.75 m). Owing to different flume widths, the blockage ratios differed between the flumes for the macrophytes (c. 7% and c. 22% at intermediate flow rates) and the cylinder (2.5% and 7.5%). For theoretically identical mean cross‐sectional velocities, the between‐flume difference in mean centreline channel velocities across the range of flows used in this study was 6.4%, indicating similar bulk flow conditions for the two flumes. We found no between‐flume differences in drag‐velocity relationships for the cylinder, whereas one macrophyte had a distinctly higher drag in the narrower flume at low approach velocities (c. 0.2 m s –1 ). This difference of drag on the macrophyte likely indicates blockage effects in the narrower flume at low velocities, when plant bending and streamlining was low. At higher approach velocities, between‐flume differences in drag on the macrophytes were minor, except for one type of macrophyte that had a higher drag at the highest velocity in the wider flume (possibly related to plant reconfiguration and fluttering).

NeuroAIDS, Drug Abuse, and Inflammation: Building Collaborative Research Activities - Joan W. Berman; Monica J. Carson; Linda Chang; Brian M. Cox; Howard S. Fox; R. Gilberto Gonzalez; Glen R. Hanson; Kurt F. Hauser; Wen-Zhe Ho; Jau-Shyong Hong; Eugene O. Major; William F. Maragos; et al. (Journal of Neuroimmune Pharmacology, 2006)

North European last glacial–interglacial transition (LGIT; 15–9 ka) tephrochronology: extended limits and new events - C. S. M. Turney; K. Van Den Burg; S. Wastegård; S. M. Davies; N. J. Whitehouse; J. R. Pilcher; C. Callaghan (Journal of Quaternary Science, 2006)
High‐precision correlation of palaeoclimatic and palaeoenvironmental records is crucial for testing hypotheses of synchronous change. Although radiocarbon is the traditional method for dating late Quaternary sedimentary sequences, particularly during the last glacial–interglacial transition (LGIT; 15–9 ka), there are inherent problems with the method, particularly during periods of climate change which are often accompanied by major perturbations in atmospheric radiocarbon content. An alternative method is the use of tephras that act as time‐parallel marker horizons. Within Europe, numerous volcanic centres are known to have erupted during the LGIT, providing considerable potential for high‐precision correlation independent of past radiocarbon fluctuations. Here we report the first identification of the Vedde Ash and Askja Tephra in Ireland, significantly extending the known provenance of these events. We have also identified two new horizons (the Roddans Port Tephras A and B) and tentatively recognise an additional horizon from Vallensgård Mose (Denmark) that provide crucial additional chronological control for the LGIT. Two phases of the Laacher See Tephra (LST) are reported, the lower Laacher See Tephra (LLST) and probably the C2 phase of the Middle Laacher See Tephra (MLST‐C2) indicating a more northeasterly distribution of this fan than reported previously. Copyright © 2006 John Wiley & Sons, Ltd.

Microbial communities of Solanum tuberosum and magainin-producing transgenic lines - M. O’Callaghan; E. M. Gerard; N. W. Waipara; S. D. Young; T. R. Glare; P. J. Barrell; A. J. Conner (Plant and Soil, 2005)

Meningoencephalitis in Mice Infected with an Equine Herpesvirus 1 Strain KyA Recombinant Expressing Glycoprotein I and Glycoprotein E - Arthur R. Frampton; Patrick M. Smith; Yunfei Zhang; Warren D. Grafton; Tomio Matsumura; Nikolaus Osterrieder; Dennis J. O'Callaghan (Virus Genes, 2004)

Long‐term ecosystem level experiments at Toolik Lake, Alaska, and at Abisko, Northern Sweden: generalizations and differences in ecosystem and plant type responses to global change - M. T. Van Wijk; K. E. Clemmensen; G. R. Shaver; M. Williams; T. V. Callaghan; F. S. Chapin; J. H. C. Cornelissen; L. Gough; S. E. Hobbie; S. Jonasson; J. A. Lee; A. Michelsen; et al. (Global Change Biology, 2004)
Long‐term ecosystem‐level experiments, in which the environment is manipulated in a controlled manner, are important tools to predict the responses of ecosystem functioning and composition to future global change. We present the results of a meta‐analysis performed on the results of long‐term ecosystem‐level experiments near Toolik Lake, Alaska, and Abisko, Sweden. We quantified aboveground biomass responses of different arctic and subarctic ecosystems to experimental fertilization, warming and shading. We not only analysed the general patterns but also the differences in responsiveness between sites and regions. Aboveground plant biomass showed a broad similarity of responses in both locations, and also showed some important differences. In both locations, aboveground plant biomass, particularly the biomass of deciduous and graminoid plants, responded most strongly to nutrient addition. The biomass of mosses and lichens decreased in both locations as the biomass of vascular plants increased. An important difference between the two regions was the smaller positive aboveground biomass response of deciduous shrubs in Abisko as compared with Toolik Lake. Whereas in Toolik Lake Betula nana increased its dominance and replaced many of the other plant types, in Abisko all vascular plant types increased in abundance without major shifts in relative abundance. The differences between the responses of the dominant vegetation types of the Toolik Lake region, i.e. tussock tundra systems, and that of the Abisko region, i.e. heath systems, may have important implications for ecosystem development under expected patterns of global change. However, there were also large site‐specific differences within each region. Several potential mechanistic explanations for the differences between sites and regions are discussed. The response patterns show the need for analyses of joint data sets from many regions and sites, in order to uncover common responses to changes in climate across large arctic regions from regional or local responses.

Litter of the hemiparasite Bartsia alpina enhances plant growth: evidence for a functional role in nutrient cycling - Helen M. Quested; Malcolm C. Press; Terry V. Callaghan (Oecologia, 2003)

Cysticercoids of five species of Raillietina Fuhrmann, 1920 (Cestoda: Davaineidae) in ants, Pheidole sp., from emu farms in Australia - M.G. O'Callaghan; M. Davies; R.H. Andrews (Systematic Parasitology, 2003)

Is there a Relationship between Soil and Groundwater Toxicity? - P. Sheehan; R.E. Dewhurst; S. James; A. Callaghan; R. Connon; M. Crane (Environmental Geochemistry and Health, 2003)

Effects of intraperitoneal injections of saline on the alcohol and sucrose consumption of C57/BL10 mice - O'Callaghan M.; Croft A.; Little H. (Psychopharmacology, 2002)

The hemiparasitic angiosperm Bartsia alpina has the potential to accelerate decomposition in sub-arctic communities - Helen M. Quested; Malcolm C. Press; Terry V. Callaghan; Hans J. Cornelissen (Oecologia, 2002)

Population-Based Evaluation of the Ehrlichia Ruminantium MAP 1B Indirect ELISA - Trevor F. Peter; Christopher J. O'Callaghan; Graham F. Medley; Brian D. Perry; Shalt M. Semu; Suman M. Mahan (Experimental and Applied Acarology, 2001)

Comparison of Acetylcholinesterase and Glutathione S-Transferase Activity in Chironomus riparius Meigen Exposed to Chemical-Spiked Sediments - R. Kheir; H. Ibrahim; J. Lewis; A. Callaghan; M. Crane (Bulletin of Environmental Contamination and Toxicology, 2001)

CHARACTERIZATION OF A NEW RAT CELL LINE ESTABLISHED FROM 2′AAF-INDUCED COMBINED HEPATOCELLULAR CHOLANGIOCELLULAR CARCINOMA - ROSARIO GIL-BENSO; ANTONIO MARTINEZ-LORENTE; ANTONIO PELLIN-PEREZ; SAMUEL NAVARRO-FOS; M. AURELIA GREGORI-ROMERO; CARMEN CARDA; ROBERT CALLAGHAN; AMANDO PEYDRO-OLAYA; ANTONIO LLOMBART-BOSCH (In Vitro Cellular & Developmental Biology - Animal, 2001)

Low alcohol preference among the ”high alcohol preference" C57 strain of mice; preference increased by saline injections - H. J. Little; M. J. O'Callaghan; A. R. Butterworth; J. Wilson; J. Cole; W. P. Watson (Psychopharmacology, 1999)

Relative potency of controlled-release oxycodone and controlled-release morphine in a postoperative pain model - G. B. Curtis; G. H. Johnson; P. Clark; R. Taylor; J. Brown; R. O'Callaghan; M. Shi; P. G. Lacouture (European Journal of Clinical Pharmacology, 1999)

Symposia lectures - F. Parak; A. Ostermann; G. U. Nienhaus; Nobuo Niimura; William A. Eaton; Stephen J. Hagen; Eric R. Henry; James Hofrichter; Gouri Jas; Lisa Lapidus; Victor Muñoz; Chih-chen Wang; et al. (Journal of Biosciences, 1999)

Chick embryo brain cultures enriched for neurons or astroglial cells support the replication of influenza A, B, and C viruses - M. S. Parker; H. A. Spence; R. J. O’Callaghan (In Vitro Cellular & Developmental Biology - Animal, 1997)

A non-invasive measurement of phloem and xylem water flow in castor bean seedlings by nuclear magnetic resonance microimaging - W. Kckenberger; J. M. Pope; Y. Xia; K. R. Jeffrey; E. Komor; P. T. Callaghan (Planta, 1997)

The effects of UV-B radiation on European heathland species - L. O. Björn; T. V. Callaghan; I. Johnsen; J. A. Lee; Y. Manetas; N. D. Paul; M. Sonesson; A. R. Wellburn; D. Coop; H. S. Heide-Jørgensen; C. Gehrke; D. Gwynn-Jones; et al. (Plant Ecology, 1997)

Molecular and cellular targeting in the expression of foreign polypeptides in bacteria - J. -M. Clment; A. Charbit; C. Leclerc; P. Martineau; S. Muir; D. O'Callaghan; O. Popescu; S. Szmelcman; M. Hofnung (Antonie van Leeuwenhoek, 1992)